ACC703: Analysis and Application of Accounting Data / Faculty of Accountancy - UiTM, Faculty of Accountancy (Universiti Teknologi MARA (UiTM), 2017)
This subject requires students to carry out in-depth analyses of companies and other organizations using information that are publicly available such as the annual reports, stock analysts report and reports arising from regulatory and statutory requirements. Students are also expected to know other sources of information such as from the Internet and stockbrokers’ reports and be familiar with the quality of information contained in such reports. Students are encouraged to question the information provided in the financial statements, adjust the figures, if necessary, and use these information in analyzing any organization. In addition to the analytical tools necessary to carry out the detailed analysis, students are expected to be able to know and apply the theoretical framework that forms the basis of financial statement analysis.